Mechanical response of nanoporous gold - Farkas, Diana (2013)
We report the results of computational tensile and compressive tests for model bi-continuous nanoporous gold structures using atomistic simulations with empirical many-body potentials and molecular dynamics. The results are compared with the predictions of scaling laws for coarser-scale foams and with available experimental data. We find a surprising substantial tension/compression asymmetry in yield due to the surface stress that sets the filament under compression, providing a bias favoring yielding in compression. We provide a model for our results based on a ligament strength value close to the theoretical strength of Au, and the surface stress. The model predicts a significant tension/compression asymmetry for ligament sizes below ∼10 nm and pore collapse for ligament sizes below 1 nm. We also observe an unexpected compaction tendency under tension characterized by a decrease in the total volume of the sample of 15% for samples deformed under tension by 30%. The mechanism of the compaction involves a decrease in the average pore size and pore collapse resulting from plasticity within the ligaments.